Mechanical properties of High-Strength concrete with bauxite sand as partial fine aggregate replacement - Azzahra, Putri Yasmin; Teguh, Mochamad (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2025)
Concrete is a key material in Indonesia’s infrastructure development, with growing interest in sustainable alternatives to natural aggregates. This study evaluates the mechanical performance of high-strength concrete incorporating bauxite sand as a partial replacement for fine aggregate. The control mix (BMT-0) was designed with a water–cement ratio of 0.3 and a cement content of 550 kg/m³, using natural sand and crushed coarse aggregate, without any chemical admixtures. Four additional mixes (BMT-1 to BMT-4) included bauxite sand at replacement levels of 2.5%, 5%, 7.5%, and 10% by weight of fine aggregate. A total of 30 specimens were tested to assess compressive strength, splitting tensile strength, and modulus of elasticity. All mixes exceeded the minimum compressive strength requirement for high-strength concrete (41.4 MPa). The mix with 5% bauxite sand replacement (BMT-2) demonstrated the highest compressive strength (49.33 MPa) and tensile strength (3.46 MPa), while the 7.5% mix (BMT-3) achieved the highest modulus of elasticity (38,877.32 MPa). The results suggest that partial replacement of fine aggregate with 5% bauxite sand enhances concrete quality without compromising mechanical performance.